2006
DOI: 10.1007/s10741-006-9190-8
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency in congestive heart failure: Why and what to do about it?

Abstract: This article gives an overview of the current knowledge on vitamin D status in patients with congestive heart failure (CHF). A serum 25-hydroxyvitamin D level below 50 nmol/l (20 ng/ml) is generally regarded as insufficient. Available data indicate that the majority of CHF patients have 25-hydroxyvitamin D levels in the insufficiency range. Skin synthesis of vitamin D after solar ultraviolet B exposure is the most important vitamin D source for humans. However, CHF patients have relatively low outdoor activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
1
16

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 86 publications
5
84
1
16
Order By: Relevance
“…Different mechanisms are proposed as the protective factors of vitamin D in heart failure. Serum level of 25 (OH) D is a significant factor showing the vitamin D reservoir of the body [10]. Receptor of vitamin D3 (calcitriol) exists in many of the cells including cardiomyocytes, endothelial cells, neurons, and immunological cells [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different mechanisms are proposed as the protective factors of vitamin D in heart failure. Serum level of 25 (OH) D is a significant factor showing the vitamin D reservoir of the body [10]. Receptor of vitamin D3 (calcitriol) exists in many of the cells including cardiomyocytes, endothelial cells, neurons, and immunological cells [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Serum level of 25 (OH) D is a significant factor showing the vitamin D reservoir of the body [10]. Receptor of vitamin D3 (calcitriol) exists in many of the cells including cardiomyocytes, endothelial cells, neurons, and immunological cells [10,11]. Calcitriol is one of the most important regulators of the calcium metabolism and serum calcium homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…First, in vitro studies have shown that vitamin D causes an imbalance between anti-inflammatory and proinflammatory cytokines, thus decreasing the activity of nuclear factor-B, increasing the production of interleukin-10, and decreasing levels of interleukin-6, interleukin-1, interferon-␥, and tumor necrosis factor-␣. 7 Second, myocardial cells of the vascular endothelium have receptors for vitamin D 1 whose activation inhibits cell proliferation. Local production of calcitriol, the active metabolite of vitamin D, depends on circulating levels of 25-hydroxycholecalciferol, which would be increased by atorvastatin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed an increased prevalence of vitamin D deficiency among patients suffering from heart failure [1]. Zittermann et al found significantly reduced 25(OH)D and 1,25(OH)2D levels in 54 heart-failure patients when compared with 34 age-, sex-, and BMI-matched controls [82].…”
Section: Vitamin D Deficiency and Heart Failure In Adultsmentioning
confidence: 99%
“…Vitamin D deficiency is commonly observed in patients suffering from myocardial diseases [1]. Sun exposure, which induces vitamin D production in the skin, is often limited in these symptomatic, housebound patients.…”
Section: Introductionmentioning
confidence: 99%